ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGAMBILAN KREDIT DI KOPERASI SIMPAN PINJAM PUTRA MANDIRI JAYA PANDEGLANG - Siti Setiati Siti Setiati; Atik Atiatun Nafisah Atik Atiatun Nafisah (LPPM STIA Banten, 2018)
The purpose of this research is to determine the factors that affect the decision society in region Pandeglang in the credit in a Koperasi Simpan Pinjam Putra Mandiri Jaya. This research uses methods analysis descriptive and quantitative, with use analysis factor. Research was carried out in Koperasi Simpan Pinjam Putra Mandiri Jaya with the number of respondents as much as 169 people of the population as much as 292 people in region Pandeglang which become debtors in a Koperasi Simpan Pinjam Putra Mandiri Jaya. The data collected by using method of inquiry be reviwed with the analysis of factor using Statistical Program Social Scene (SPSS) versi 17.0 for windows. The results of research showed that there are four factors that influence the decision of the in region Pandeglang in the credit in a Koperasi Simpan Pinjam Putra Mandiri Jaya, is cultural factor, social factor, the personal factor, and psychological factor. Amount Variance explained each of these factor in succession, which is ,cultural factor by 53,688%, social factor 12,256% , personal factor by 9,024 % and psychological by 7,851%. Cultural factor being the most dominant influence the decision society in region Pandeglang in the credit in a Koperasi Simpan Pinjam Putra Mandir Jaya..